LAYANAN INFORMASI KARIR SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN KARIR SISWI MTS KELAS IX - Hidayati, Nazlah; Riskiyah, Riskiyah (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2022)
Guidance and counseling is a process of providing assistance to each individual or group systematically and continuously, with the aim of being able to understand oneself, the environment, and to develop one's potential optimally both in the areas of individual guidance, social, learning and also in the career field. In particular, career information services are one of the services that can increase career understanding, so MTs Sumber Mas implements these services. To find out in depth the services provided at MTs Sumber Mas, this research used descriptive qualitative research using interview, observation and documentation methods. To check the validity of the data, researchers used data/source triangulation. The results are that the level of career understanding of female students in class IX, MTs Sumber Mas Rombiya Barat Ganding has increased, which is marked by a decrease in female students who are not serious about listening, enthusiasm and their level of mastery of the various career information provided.Â